2021
DOI: 10.2196/24906
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Leadership in a Digitalized Working World and Their Effects on Employees’ Stress and Resources: Web-Based Questionnaire Study

Abstract: Background In today’s world of work, the digitalization of work and communication processes is increasing, and will increase even further. This increase in digitalization at the workplace brings many new aspects of working life to light, such as working in virtual teams, mobile working, expectations of being constantly available, and the need for support in adapting and learning new digital tools. These changes to the workplace can contain risks that might harm the well-being of employees. Leaders … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 64 publications
2
30
0
4
Order By: Relevance
“…This expands the understanding of the core competences necessary for consideration as an experienced professional and places a requirement on educational organizations and psychiatric hospitals to support health professionals in fulfilling this aim. Recent findings also highlight the importance of leaders investing in technical support for their employees, such as “receiving low support in learning and using digital tools” [ 46 ], which is expected to contribute to enhanced digital competence [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…This expands the understanding of the core competences necessary for consideration as an experienced professional and places a requirement on educational organizations and psychiatric hospitals to support health professionals in fulfilling this aim. Recent findings also highlight the importance of leaders investing in technical support for their employees, such as “receiving low support in learning and using digital tools” [ 46 ], which is expected to contribute to enhanced digital competence [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…And lastly, the study by Bregenzer and Jimenez ( 2021 ) revealed that risk factors of digital work (distributed team work, mobile work, constant availability, and inefficient technical support) were positively associated with stress perceptions among employees. Health-promoting leadership was negatively associated with stress perceptions (ß = −0.31, p < 0.001).…”
Section: Resultsmentioning
confidence: 99%
“…Again, this could be where individual goal setting can support people feeling they can achieve their targets and improve over time. However, as scholars [ 40 ] have observed in the study of mHealth tools in the workplace, such tools allow for a systematic review of progress; however, this is put at risk where there is an over-emphasis on health evaluation, and employees feel obliged to use such tools.…”
Section: Resultsmentioning
confidence: 99%